1985
DOI: 10.7164/antibiotics.38.1034
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and chemical structure of aklanonic acid, an early intermediate in the biosynthesis of anthracyclines.

Abstract: The fermentation, isolation and structure elucidation of aklanonic acid are described. The compound was isolated from fermentations of Streptomyces strain ZIMET 43,717. Aklanonic acid is a yellow-orange crystalline substance, melting at 203-204'C (dec), having the molecular formula C:1H1sOs, and possessing UV maxima at 258, 282 (sh) and 438 nm (CHCI3). In dimethyl sulfoxide or pyridine aklanonic acid is unstable and a new compound (aklanone) is formed as a conversion product.The elucidation of the structures h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 10 publications
3
25
0
Order By: Relevance
“…For extraction, the pH of each culture broth was adjusted to 1.5 with 6 N HCl, and the acidified broths were extracted with an equal volume of chloroform, reduced to dryness, and reconstituted in 100 l of chloroform. Aklanonic acid produced by the recombinant strains was compared with authentic aklanonic acid obtained from K. Eckardt (9) in parallel and by cochromatography, using TLC as described previously (4). Aklanonic acid also was analyzed by HPLC as previously described (4, 7), using a C 18 reverse-phase column and a solvent system of methanol:water:glacial acetic acid (65:30:5) (4).…”
Section: Gene Disruption Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For extraction, the pH of each culture broth was adjusted to 1.5 with 6 N HCl, and the acidified broths were extracted with an equal volume of chloroform, reduced to dryness, and reconstituted in 100 l of chloroform. Aklanonic acid produced by the recombinant strains was compared with authentic aklanonic acid obtained from K. Eckardt (9) in parallel and by cochromatography, using TLC as described previously (4). Aklanonic acid also was analyzed by HPLC as previously described (4, 7), using a C 18 reverse-phase column and a solvent system of methanol:water:glacial acetic acid (65:30:5) (4).…”
Section: Gene Disruption Methodsmentioning
confidence: 99%
“…strain C5 and Streptomyces peucetius ATCC 29050, are synthesized by condensation of nine extender units derived from malonyl coenzyme A (CoA) onto a propionyl moiety to make a theoretical C 21 polyketide intermediate (16,(33)(34)(35) which is reduced at C-9 (34), cyclized, and aromatized to form aklanonic acid ( Fig. 1), the first characterized chromophore in these pathways (9,16,(33)(34)(35). Aklanonic acid is converted in four enzymatic steps to ε-rhodomycinone (1,4,(33)(34)(35), which is then glycosylated and modified by a series of reactions to form daunorubicin and doxorubicin (6,16,33,35).…”
mentioning
confidence: 99%
“…C5 dauA mutants. Eckardt et al (1985) isolated aklanonic acid, an anthraquinone metabolite accumulated by Streptomyces sp. ZIMET 437 17, and showed that this compound and its chemically produced methyl ester could be converted in vivo by blocked mutants of the daunomycin-producing strain, S. griseus IMET JA 5142, to aklavinone, an intermediate in daunomycin biosynthesis .…”
Section: Extract Feeding Experiments To Establish a Biosynthetic Sequmentioning
confidence: 99%
“…This suggests that aklanonic acid or analogous anthraquinones may be universal intermediates in the formation of various naphthacenequinone polyketides. AAME and aklaviketone have previously been converted to anthracyclines in vivo Eckardt et al, 1985;Schumann et al, 1986). When spores of the maggiemycin-accumulating dauE mutant, SC5-24, were treated with NTG, doubly-mutated strains that accumulated aklanonic acid (dauC, E), AAME (dauD, E ) or aklaviketone (dauE, F ) were isolated.…”
Section: Extract Feeding Experiments To Establish a Biosynthetic Sequmentioning
confidence: 99%
“…1) are clinically important anthracycline chemotherapeutic agents (2, 11, 17), which are synthesized by a type II polyketide synthase (23,(42)(43)(44). The aglycone is formed by condensing nine extender units derived from malonyl coenzyme A onto a propionyl moiety to make a C 21 polyketide intermediate (21,23,(42)(43)(44)(45)50), which is reduced at C-9 from the carboxy terminus (43, 44), cyclized, and aromatized to form aklanonic acid (18,19,23,40,(42)(43)(44). Aklanonic acid is converted in four steps to ε-rhodomycinone (3,7,15,16,30,40,42,44), an intermediate that is accumulated in large quantities by most daunorubicin-producing strains (27,42,44,46).…”
mentioning
confidence: 99%